Introduction to the Special Issue: Restructuring and Resisting Education Reforms in Chicago’s Public Schools - Gutierrez, Rhoda Rae; Waitoller, Federico R. (Education Policy Analysis Archives, 2017)
In this paper, guest editors Gutierrez and Waitoller introduce the special issue, Restructuring and Resisting Education Reforms in Chicago’s Public Schools. As a pioneer of neoliberal education reforms, the city of Chicago and its public school system offers a rich context for critical policy scholarship on the dialectic between education restructuring and community resistance against these reforms. First, the authors contextualize Chicago education reforms within the larger neoliberal project by providing an overview of the policies driving the closures of traditional public schools and expansion of charter schools that the contributors to this special issue examine. The authors also address the co-constitutive nature of race and neoliberalism in education policy, and the disproportionate impact these policies have on low-income communities of color. Next, the authors discuss the significance of this collection of papers for educational policy analysis and call for more research that situates examinations of urban educational reforms in their specific socio-historical, political, and economic contexts. The paper concludes with a summary of the articles included in the special issue.